2021
DOI: 10.3390/su13126856
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Varietal Selection for Promising Rice Lines

Abstract: The purpose of rice breeding is to create varieties that are well adapted, highly productive, and acceptable to farmers. However, rice productivity is limited as a result of combined biotic stresses (pests/diseases). This study combines assessment by farmers with the evaluation by breeders with respect to promising rice lines within a range of environments. The aim is to investigate farmers’ preferences and to characterize the yield of promising rice lines, as well as their resistance to pests/diseases by cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Participatory Varietal Selection (PVS), that was launched at the Lumle Agriculture Center in 1989-1990, seems to be an effective strategy because it evaluates, confirms, and promotes new rice cultivars while taking into account the socio-technological context of the end-users and highlights their preferences (Kosanke, 2019). The PVS technique has been using indigenous knowledge to accelerate the adoption of emerging types of rice genotypes (Aristya et al, 2021). Drought stress is significant due to main five factors: its unpredictable nature, manner of occurrence, severity, length, and timing (Abarshahr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Participatory Varietal Selection (PVS), that was launched at the Lumle Agriculture Center in 1989-1990, seems to be an effective strategy because it evaluates, confirms, and promotes new rice cultivars while taking into account the socio-technological context of the end-users and highlights their preferences (Kosanke, 2019). The PVS technique has been using indigenous knowledge to accelerate the adoption of emerging types of rice genotypes (Aristya et al, 2021). Drought stress is significant due to main five factors: its unpredictable nature, manner of occurrence, severity, length, and timing (Abarshahr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…If varieties are sufficient according to farmers' preferences, the availability of seeds was limited when farmers needed them. Each rice variety will provide optimal results if planted in the appropriate field [25].…”
Section: Rice-irrigated Farming Performancesmentioning
confidence: 99%
“…Therefore, location-specific rice cultivars should be selected to obtain high yields. Aristya et al (2021) reported that GM 28 has the highest mean yield per hectare (6.980 tons ha −1 ) in an irrigated paddy field in three districts in Central Java Province, Indonesia.…”
Section: Stability Variance Estimates Through Gge-biplotmentioning
confidence: 99%